Sustainable Hybrid Cooling: Integrating Indirect Evaporative and Split Air Conditioning for Improved Indoor Air Quality in Tropical Climates - Tassanu Ruangsuwan; Wantanee Phanprasit; Witaya Yoosook; Vorakamol Boonyayothin; Pajaree Konthonbut; John W. Cherrie; Noppanun Nankongnab (Buildings)
To address the limitations of conventional split air conditioners (SACs) that lack proper ventilation, resulting in indoor pollutant buildup and health risks, this study develops and evaluates the performance of a sustainable hybrid air conditioning system that integrates Indirect Evaporative Cooling (IEC) with SAC to enhance indoor air quality (IAQ), thermal comfort, and energy efficiency in tropical climates, compared with a standalone SAC system. The hybrid SAC + IEC system is designed to meet stringent comfort criteria while reducing indoor formaldehyde and carbon dioxide concentrations. Experiments were conducted in a controlled classroom environment using a cross-flow tubular heat exchanger with optimized nozzle configurations. Temperature, humidity, and pollutant levels were continuously monitored under varying tropical conditions. The IEC achieved an average cooling capacity of 1430 W, substantially exceeding the target of 566 W, and reduced the fresh air dry-bulb temperature by up to 8.79 °C, maintaining primary air near 25.2 °C, with energy efficiency ratios varying between 30% and 100%. The hybrid SAC + IEC system outperforms the standalone SAC system in maintaining acceptable formaldehyde and CO2 levels while delivering comfortable thermal conditions within the indoor standards. These results demonstrate that the Hybrid SAC + IEC system optimizes energy efficiency and improves cooling performance and indoor air quality (IAQ) for tropical environments.